2023
DOI: 10.3389/fncel.2023.1132015
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of DLD-mediated cuproptosis induced spinal cord injury and its regulation on immune microenvironment

Abstract: IntroductionSpinal cord injury (SCI) is a severe central nervous system injury that leads to significant sensory and motor impairment. Copper, an essential trace element in the human body, plays a vital role in various biological functions and is strictly regulated by copper chaperones and transporters. Cuproptosis, a novel type of metal ion-induced cell death, is distinct from iron deprivation. Copper deprivation is closely associated with mitochondrial metabolism and mediated by protein fatty acid acylation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Studies have reported that cuprotosis plays a role in signal transduction and regulates the etiology, severity, and progression of cancer. It not only plays a role in chronic diseases but also participates in the occurrence and development of various acute diseases, such as acute myocardial infarction and acute spinal cord injury (7)(8)(9). Cuprotosis, an intervention target for copper metabolism disorders, may be a novel approach for treating various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that cuprotosis plays a role in signal transduction and regulates the etiology, severity, and progression of cancer. It not only plays a role in chronic diseases but also participates in the occurrence and development of various acute diseases, such as acute myocardial infarction and acute spinal cord injury (7)(8)(9). Cuprotosis, an intervention target for copper metabolism disorders, may be a novel approach for treating various diseases.…”
Section: Introductionmentioning
confidence: 99%